IMPLEMENTASI APLIKASI MEDIA TALITINA SEBAGAI SARANA MEMPERMUDAH BELAJAR PERKALIAN BAGI PESERTA DIDIK SD DI KELAS IV - Damayanti, Sehla Safira; Afrianingsih, Anita (Universitas Islam Nahdlatul Ulama Jepara, 2023)
TALITINA media is a media that is able to facilitate students in learning multiplication calculations, so that its implementation is easy to practice both in learning conditions at home or at school. The purpose of this study was to determine the activities of implementing the TALITINA media application as a means of facilitating multiplication learning for elementary school students. Methods for data collection used were observation, interviews and documentation. The results of the study indicate that the TALITINA media has a positive impact on increasing student competence, especially in the multiplication calculation indicator.Â keywords:Â applications, TALITINA media, and students